STUDY THE EFFICACY OF TAMSULOSIN AND PREDNISOLONE IN THE MEDICAL MANAGEMENT OF PELVIC URETERAL STONES - القادري, احمد; أيمن حرفوش; محمد كنعان (Latakia University Journal -Medical Sciences Series, 2023)
The Aim:Study of the effectiveness of combined medical treatment between alpha-adrenergic blockers (tamsulosin) and corticosteroids (prednisolone) in the medical-expulsive therapy of ureteropelvic stones. * Patients and methods: The study sample consisted of (70) with a radiologically proven distal ureteral stone and were eligible for inclusion in this study and were systematically distributed into two groups Group A: receive treatment with tamsulosin 0.4 mg for 28 days/ Group B: receive treatment with tamsulosin 0.4 mg for 28 days + prednisolone 20 mg for 10 days/ Tramadol or diclofenac potassium was also prescribed for pain relief * Results: The age range was 19-69 years and a mean age of 45.32 years. There were statistically significant differences between the two groups regarding the rate of stone expulsion after 10 days of treatment, ,and average values of the expulsion time ,and the median values for the duration of taking analgesics, and the success rate of treatment, which were better in group B and compared to group A *Recommendations and Suggestions: Greater expulsion rate, more rapid stone expulsion , and less use of analgesics when prednisolone is combined with tamsulosin in the treatment of distal ureteral stones.